A formação inicial do professor dos anos iniciais do ensino fundamental para o ensino de ciências - Pires, Elocir Aparecida Corrêa (2017)
Faced with the intense production of new knowledge and its rapid dissemination, Science Education becomes of great importance already in the first years of Basic Education. Such importance is due to the possibility of this education contribute to the critical and citizen formation of the subjects, providing opportunities for the use of scientific and technological knowledge to better understand the world they live in. However, the literature of the area has pointed out that the teachers who work at this educational level, in particular in the Initial Years of Elementary School, present great difficulties in teaching science. From this perspective, we have as proposal of discussion, in this work, the process of formation of this professional. The problem that we present, from the object of this investigation, is: How has the formation of pedagogues occurred, considering their preparation to act in the process of teaching and learning of Science in the Early Years of Elementary School? The present work sought to understand if, in the perception of the subjects involved in this process of initial formation (teachers of the discipline of Sciences, coordinators of the courses, advisors of the Teaching Practice and undergraduate students) of the presential course of Pedagogy, this has provided knowledge to act with the Discipline of science. Seeking for answers, three instruments were used: bibliographical, documentary and field research. This research, qualitative, chose as scenario of investigation the context of four Institutions of Higher Education that offer the presential course of Pedagogy in the city of Cascavel - PR, Brazil. Based on the Content Analysis, the material was collected and interpreted through interviews with the coordinators of the Pedagogy courses, teachers who work with the discipline corresponding to Science Education and supervised Internship advisors, as well as a questionnaire to the graduating students of the course. The results of the research indicate that the Pedagogy course contributes with practical-methodological knowledge, for the teaching performance in the Initial Years of Elementary School. However, the specific knowledge remains in superficiality, since, given the reduced workload, it is not possible to encompass the breadth of knowledge related to the content required for this professional's performance. In particular in the area of Science Education, the answers about the production of scientific knowledge nature are close to a hierarchical perspective, without contextualization of the information, through rules, classifications and closed formulas. In this direction, Science Education was characterized by the research subjects as a process that seeks the final product of scientific knowledge, based solely on the transmission of knowledge, a perspective in which the construction of knowledge by the student ends up being underprivileged. These results indicate the need to broaden the teaching time, as well as to review the ways in which they are introduced in Pedagogy courses, in order to promote approaches that contemplate discussions not only on pedagogical methodologies, but epistemological reflections. That is, to promote actions that will awaken, in the initial formation of educational professionals, a critical-reflexive position on the teaching action in Science Education, so that its practice does not remain restricted to dogmatic approaches to the production of scientific knowledge.